Review of the Malagasy lecithocerid species described by Pierre Viette and deposited in MNHN (Paris), with new generic combinations and descriptions of a new subfamily and genus of Momphidae (Lepidoptera: Gelechioidea) - Park, Kyu-Tek; Koo, Jun-Mo; Minet, Joël (Zootaxa, 2020)
The holotypes of the Malagasy Lecithoceridae described by Pierre Viette (from 1954 to 1988) are reviewed, which represents a total of 23 specimens originally assigned to the genera Idiopteryx Walsingham, 1891 (4 named species) and Lecithocera Herrich-Shäffer, 1853 (19 named species). The holotype of Nemophora janineae Viette, 1954, erroneously described in Adelidae, is also included in the present study since it clearly belongs to the Lecithoceridae; N. janineae is here transferred to the genus Parkiana Cho, 2020. All these type specimens are housed in the Muséum National d’Histoire Naturelle (MNHN, Paris), where Pierre Viette had worked as a researcher during almost forty years (1945–1982). The Lecithocera species in question are transferred either to other genera of the Lecithoceridae, or to other families: 12 species, including Lecithocera kambanella and L. masoalella previously transferred by Park (2018), are assigned to Torodora Meyrick, 1894; three species to Parkiana Cho; the remaining species to non-lecithocerid groups, namely the Gelechiidae: Dichomeridinae (1 species), the Epichostis-group (considered incertae sedis but here expanded to include the genus Merocrates Meyrick, 1931; 1 species), and the Momphidae (2 described species, here regarded as synonyms, viz. L. andrianella Viette, 1968 and L. ranavaloella Viette, 1968). The four alleged Malagasy Idiopteryx turn out to belong to non-lecithocerid families and are transferred to the genera Dichomeris Hübner (Gelechiidae: Dichomeridinae; 1 species), Odites Walsingham (Peleopodidae: Oditinae; 1 species), and Moca Walker (Immidae, superfamily Immoidea; 2 species). Within the Momphidae, Lecithocera andrianella Viette is assigned to a new genus, Adelomompha Minet & Park gen. nov., which is placed in a new subfamily (Adelomomphinae Minet & Park subfam. nov.) since it lacks at least two imaginal apomorphies present in the ground plan of the remaining Momphidae (here placed in the subfamily Momphinae, revised status). High resolution photographs were taken to illustrate the habitus and various morphological structures (genitalia, notably) of the 24 above-mentioned type specimens (MNHN material).